Effect Financial Ratio, Company Age, Size Public Accountant Firm In Audit Delay - Julia, Julia (Jurnal Akuntansi, 2020)
The accuracy in submission of financial statements is a condition where the company must accurately and timely calculate the report before being audited by public accountants. The purpose of this study was to Determine the effect of profitability, solvability, liquidity, company age and size of the public accounting firm with size as control variables on audit delay either simultaneously or partially. The population in this study was the mining companies listed on the Indonesia Stock Exchange in 2015-2017 and used 37 samples companies. The statistical analysis used in this study was the data panel regression analysis and continued testing of hypotheses with EViews version 9.0 software program. Based on the results of the analysis, it was concluded that the variable of profitability, liquidity, and age of company had no significant effect on audit delay. solvability, size of public accounting firm, and company size had a significant effect on audit delay.